2005
DOI: 10.1017/s0033291704003253
|View full text |Cite
|
Sign up to set email alerts
|

Admixture analysis of age at onset in obsessive–compulsive disorder

Abstract: These results, based on a statistically validated AAO cut-off and those of previous studies on AAO in OCD, suggest that AAO is a crucial phenotypic characteristic in understanding the genetic basis of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
4
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 30 publications
8
79
4
2
Order By: Relevance
“…Our data indicate that the majority of patients experience significant symptoms before age 21, with only minor gender differences (figure 1). Of note, these data and those of others indicate a unimodal, non-normal distribution of age of OCD-related impairment [16], unlike some prior suggestions that age of OCD onset might have a bimodal pattern, with separate peaks in childhood and in adulthood [17].…”
Section: Obsessive-compulsive Disorder: a Brief Overview Of Phenomenocontrasting
confidence: 81%
“…Our data indicate that the majority of patients experience significant symptoms before age 21, with only minor gender differences (figure 1). Of note, these data and those of others indicate a unimodal, non-normal distribution of age of OCD-related impairment [16], unlike some prior suggestions that age of OCD onset might have a bimodal pattern, with separate peaks in childhood and in adulthood [17].…”
Section: Obsessive-compulsive Disorder: a Brief Overview Of Phenomenocontrasting
confidence: 81%
“…33 A closer look at the heritability estimates over time reveals that OCS is remarkably stable, with heritability estimates of approximately 55% at younger ages, 11 with a decrease at age 12, in which part of the variance was accounted for by shared environmental influences, continuing to 55% at ages 14 and 16, and 45% in adulthood. 15 This decrease in heritability between children/adolescents and adults may reflect the bimodal distribution found in the clinical OCD literature, 1,2 which found early-onset OCD to be associated with a higher genetic load compared to late-onset OCD.…”
Section: Discussionmentioning
confidence: 93%
“…In OCD, a bimodal distribution of age at onset has been found, with one peak occurring in preadolescent childhood and another peak in adulthood. 1,2 Early age at onset of OCD is also associated with tic disorder, 3,4 and the morbidity risk of OCD in family members of OCD subjects with early-onset OCD is higher than in relatives of late-onset OCD probands. 5,6 Furthermore, adult studies found an equal representation of men and women with OCD, or a slight female preponderance, whereas in clinical studies, early age at onset of OCD is associated with male preponderance.…”
mentioning
confidence: 99%
“…Previous studies suggest that age of onset in OCD has two distributions [Delorme et al, 2005]. Moreover, early onset OCD has been found to represent a more familial phenotype of the disorder [Lenane et al, 1990;Pauls et al, 1995;Delorme et al, 2005].…”
Section: Discussionmentioning
confidence: 99%